Kinetics of the Reactions Prevailing during Packed‐Bed Chemical Looping Combustion of Syngas using Ilmenite. Issue 10 (11th May 2016) - Ortiz, Maria; Gallucci, Fausto; Melchiori, Tommaso; Spallina, Vincenzo; van Sint Annaland, Martin
Abstract: Chemical looping combustion has been identified as a very promising technology for power production with integrated carbon dioxide capture. The objective of this work is to study the kinetics of all reactions that are important in the combustion of syngas in a packed‐bed chemical looping reactor by using ilmenite as an oxygen carrier. The reaction kinetics of reduction, with hydrogen and carbon monoxide, and oxidation, with oxygen, of ilmenite‐based pellets have been determined in a thermogravimetric analyzer. The shrinking core model for a spherical geometry was used to obtain the kinetic parameters by considering mixed control by chemical reactions and diffusion through the product layer for all reaction involved. The reduction rate of ilmenite by hydrogen was at least an order of magnitude higher than that by carbon monoxide (especially at higher particle conversions) and the activation energies were found to be 45 and 30 kJ mol −1 for reduction with hydrogen and carbon monoxide, respectively. For the oxidation reaction, a much lower apparent activation energy of 5 kJ mol −1 was found, which indicated that the temperature did not have an important effect on the oxidation kinetics of ilmenite. In addition, the catalytic activity of ilmenite for water gas shift (WGS) was measured in a micro fixed‐bed reactor. An empirical power‐law model was used to describe the kinetics of the WGS reaction over ilmenite. Abstract : Extra loop features : Chemical looping combustion has been identified as a very promising technology for power production with integrated carbon dioxide capture. The kinetics of all reactions that are important in the combustion of syngas in a packed‐bed chemical looping reactor by using ilmenite as an oxygen carrier are discussed.